Study of Selected BRCA1, BRCA2, and PIK3CA Mutations in Benign and Malignant Lesions of Anogenital Mammary-Like Glands - Konstantinova, Anastasia M; Shelekhova, Ksenya V; Imyanitov, Evgeny N; Iyevleva, Aglaya; Kacerovska, Denisa; Michal, Michal; Kazakov, Dmitry V (The American Journal of dermatopathology, 2017)
Anogenital mammary-like glands (AGMLGs) are nowadays considered a normal component of the anogenital area. Lesions involving AGMLGs are histopathologically very similar to their mammary counterparts, but the information on molecular biological mechanisms in these vulvar/perianal tumors is scarce. Mutations in the PI3K-AKT cascade have been found in hidradenoma papilliferum. The authors studied selected BRCA1, BRCA2, and PIK3CA mutations in series of benign and malignant neoplasms thought to be associated with AGMLGs, including 9 cases of primary extramammary Paget disease, 3 different cases of mammary-type carcinoma (adenoid cystic like, tubulolobular, and invasive ductal like), and 5 cases of hidradenoma papilliferum. No BRCA mutation was detected, whereas 3 neoplasms yielded PIK3CA mutation, including extramammary Paget disease, mammary-type invasive ductal carcinoma, and tubulolobular carcinoma. Our study expands the spectrum of lesions of AGMLGs harboring mutations in genes encoding the PI3K-AKT cascade. Further studies of the whole BRCA1 and BRCA2 genes using a larger cohort are needed to clarify their role in the pathogenesis of AGMLG lesions.
Keywords: nádory vulvy; senioři; Class I Phosphatidylinositol 3-Kinases; jehlová biopsie; senioři nad 80 let; Mammary Glands, Human; protein BRCA2; Retrospective Studies; Prognosis; regulace genové exprese u nádorů; imunohistochemie; nádory anu; Cohort Studies; Risk Assessment; Biopsy, Needle; Middle Aged; extramamární Pagetova nemoc; mutace; fosfatidylinositol-3-kinasy třídy I; kohortové studie; mléčné žlázy lidské; Aged, 80 and over; Immunohistochemistry; ženské pohlaví; prognóza; hodnocení rizik; Mutation; retrospektivní studie; Gene Expression Regulation, Neoplastic; Humans; Anus Neoplasms; lidé středního věku; BRCA2 Protein; BRCA1 Protein; protein BRCA1; Female; Aged; Vulvar Neoplasms; Paget Disease, Extramammary; lidé